An Investigation into Irish Primary Teachers' Perceptions of Mindfulness - Danaher, Orla (My University, 2019)
In recent years mindfulness-based practices have begun to permeate classrooms throughout Ireland, resulting in the need for additional research focusing on the experiences and perceptions of the teachers carrying out the practice. This study examines the experiences and perceptions of eleven Irish primary school teachers surrounding their implementation of mindfulness-based practices in the classroom. Three main themes emerged in the findings, the motivating factors behind the inclusion of mindfulness practices in the classroom, the benefits teachers found after incorporating mindfulness into the classroom and finally, the challenges confronting teachers when incorporating mindfulness into the classroom. The findings that emerged suggest that teachers are open and willing to incorporate mindfulness practices into the classroom, however the lack of time available in an already overloaded curriculum appeared to be the main obstacle in the implementation of the practice. To encapsulate, there is need now, more than ever, for mindfulness interventions to be incorporated in schools throughout Ireland to provide children with the necessary tools and skills to alleviate stress and worry. Mental health issues experienced by primary school children in Ireland have escalated in recent years. Evidently there is need for the provision of tools, time and resources to enable teachers to incorporate a comprehensive mindfulness programme into the school curriculum.
Professional Master of Education
Keywords: Research Subject Categories; Mindfulness; Classroom; Stress; Mental health